Additional Risk factors for infection by multidrug-resistant pathogens in healthcare associated infection: a large cohort study - Cardoso, T. (2012)
BACKGROUND: There is a lack of consensus regarding the definition of risk factors for healthcare-associated infection (HCAI). The purpose of this study was to identify additional risk factors for HCAI, which are not included in the current definition of HCAI, associated with infection by multidrug-resistant (MDR) pathogens, in all hospitalized infected patients from the community. METHODS: This 1-year prospective cohort study included all patients with infection admitted to a large, tertiary care, university hospital. Risk factors not included in the HCAI definition, and independently associated with MDR pathogen infection, namely MDR Gram-negative (MDR-GN) and ESKAPE microorganisms (vancomycin-resistant Enterococcus faecium, methicillin-resistant Staphylococcus aureus, extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella species, carbapenem-hydrolyzing Klebsiella pneumonia and MDR Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter species), were identified by logistic regression among patients admitted from the community (either with community-acquired or HCAI). RESULTS: There were 1035 patients with infection, 718 from the community. Of these, 439 (61%) had microbiologic documentation; 123 were MDR (28%). Among MDR: 104 (85%) had MDR-GN and 41 (33%) had an ESKAPE infection. Independent risk factors associated with MDR and MDR-GN infection were: age (adjusted odds ratio (OR) = 1.7 and 1.5, p = 0.001 and p = 0.009, respectively), and hospitalization in the previous year (between 4 and 12 months previously) (adjusted OR = 2.0 and 1,7, p = 0.008 and p = 0.048, respectively). Infection by pathogens from the ESKAPE group was independently associated with previous antibiotic therapy (adjusted OR = 7.2, p < 0.001) and a Karnofsky index <70 (adjusted OR = 3.7, p = 0.003). Patients with infection by MDR, MDR-GN and pathogens from the ESKAPE group had significantly higher rates of inadequate antibiotic therapy than those without (46% vs 7%, 44% vs 10%, 61% vs 15%, respectively, p < 0.001). CONCLUSIONS: This study suggests that the inclusion of additional risk factors in the current definition of HCAI for MDR pathogen infection, namely age >60 years, Karnofsky index <70, hospitalization in the previous year, and previous antibiotic therapy, may be clinically beneficial for early diagnosis, which may decrease the rate of inadequate antibiotic therapy among these patients.